Patorani local knowledge system in fisheries resources conservation education in Galesong District South Sulawesi - Hasriyanti Hasriyanti; Rusdi Rusdi; Erman Syarif; Titus Adeyemi Alonge (Universitas Negeri Malang, 2023)
The development of fishery resources is realized through one of the pillars of development, namely pro-environment (restoration and preservation of the environment) in the order of conservation and rehabilitation of marine resources. This study aimed to investigate and describe patorani culture, which is the local fishermen's knowledge of conserving fishery resources. This research used the qualitative descriptive method with a phenomenological approach by using several sets of data, including the preliminary studies. The data were collected through literature review, observation, and preliminary survey, and then they were analyzed based on understanding and public opinion through a qualitative approach. The informant is a patorani fisherman who act as the papalele, punggawa, and sawi. Primary data sources and data collection techniques are obtained mostly from participation observation, and in-depth interviews with patorani fishermen families. The data obtained were analyzed componential through three stages, namely data reduction, data presentation, and data verification. The results of this study showed that Galesong society still practices patorani culture in the utilization of coastal resources and maritime transport, including: 1) knowledge related to ceremonial preparation of fishing activities, 2) the use of technology fishing gear, 3) knowledge about the existence of spear fish, 4) knowledge in fishing activities, and 5) knowledge of the fishing voyage patorani. The fisherman's knowledge of patorani culture was derived from hereditary experience. Patorani’s knowledge comes from empirical reality as a result of interaction with the environment, both with the human environment itself and the natural environment of the sea. Finally, the local knowledge system of patorani can systematically support education on the conservation of aquatic biological resources, especially fishery resources.